Study on shear behavior and capacity of biaxial ellipsoidal voided slabs. (October 2020) - Amoushahi Khouzani, Mohsen; Zeynalian, Mehran; Hashemi, Mahmoud; Mostofinejad, Davood; Farahbod, Farhang
Abstract: The numerous advantages of solid slabs, including adequate rigidity, appropriate fire resistance, and sound insulation, have further extended the system's applications. The main disadvantage of this system is, however, its extreme weight, especially in long spans. Since concrete is not involved in bearing in the tensile zone, its removal can lower the weight without affecting the load bearing of the slab. In a number of systems, named biaxial voided slabs, ellipsoidal or spherical sacrificial plastic balls are used to create voids within the concrete. As this system has just been introduced, considerable uncertainties have been raised about one-way and two-way shear behaviors of the system. Accordingly, four full-scale specimens were built in order to investigate these behaviors. Two one-way and two two-way full-scale shear specimens with dimensions of 3500 × 1200 × 200 mm and 2300 × 2300 × 200 mm (length × width × height) were constructed, respectively. These specimens were used to compare the shear capacity, cracking distribution, and deflection in solid and biaxial voided specimens. Also, the effect of vertical rods of steel cages on the shear behavior was investigated. The results show the steel cages clearly contributed to shear bearing; and although the shear capacity of voided specimens was less than solid ones, the failure mode of all specimens was shear. Finally, a new method was proposed to predict the ratio of shear capacity of biaxial voided slabs to solid slabs. Hence, the proposed method can predict the ratio of biaxial voided capacity to solid slab capacity with an adequate precision.